Bacillus subtilis para el control de Rhizoctonia solani en arroz (Oryza sativa) en la provincia de Los Ríos - Rodríguez Ramírez, Mario Airto (2021)
Rice in ecuadorian basket is the first main product for the entire national population, making it the most commercially marketed grass on the domestic market. The province of Los Ríos is a purely agrarian region, and rice activity is one of the main agricultural activities that take place in all cantons of the region. It is therefore the crop that generates labor supply directly and indirectly in the rural and urban area of the province. The use of microorganisms that control the presence of fungal spores that cause disease in rice crops, are of great importance their application. The research was subjected to analysis technique and summary where everything related to the control of Rhizoctonia solani was discussed with the use of bacillus subtilis bacteria as fungicide. In the province of Los Ríos there is an influence as to the dosage used on the presence of the fungus Rhizoctonia solani in rice crops. Dosages of 1.0 and 4.0 liters per hectare of fungicide containing Bacillus subtilis as an active ingredient, is effective in controlling the named fungus, as the dosage of 0.4 liters per hectare is not recommended.